Study of Progress Expected Results Based on Percentage of Construction Work Plan Duration - Mardiaman Mardiaman; Edward Kusuma (Litbang Pemas - Universitas Islam Lamongan, 2021)
Abstract. Controlling how construction work is completed is critical to success. Generally, the result value method is used as the tool. Although this method has been applied to a variety of different types of construction work, the tool has been limited to a single project. This study examines the total value of completed construction work. Because the duration of construction work varies, the researchers refer to the percentage of the plan's duration. The percentages are set at 25%, 30%, and 50%. There have been 17 completed building construction projects between 2017 and 2018. Additionally, a comparison sample of construction work is used. The results of the data processing are pessimistic, most likely, optimistic, and hopeful. Additionally, the expected value is compared to a reference value. The expected values for the percentages of 25%, 30%, and 50% are (-2.425), (1.071), and 50%, respectively (2.275). Indeed, the expected value obtained is not the same as the comparison value. The contractor can prepare the necessary resources by knowing the value of the expected yield at a certain percentage of the duration.